2008
DOI: 10.1016/j.neuroscience.2008.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Forced and voluntary exercise differentially affect brain and behavior

Abstract: Abstract-The potential of physical exercise to decrease body weight, alleviate depression, combat aging and enhance cognition has been well-supported by research studies. However, exercise regimens vary widely across experiments, raising the question of whether there is an optimal form, intensity and duration of exertion that would produce maximal benefits. In particular, a comparison of forced and voluntary exercise is needed, since the results of several prior studies suggest that they may differentially aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
197
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(217 citation statements)
references
References 60 publications
9
197
1
4
Order By: Relevance
“…Habitual voluntary long-term exercise is believed to have a beneficial effect on human behavior and sleep [43,44]. Moreover, rodents using a running wheel voluntarily for a long period showed beneficial effects on behavior [45][46][47]. In a preliminary experiment on novelty-induced activity by means of an open-field test, Ex-mice at 25 weeks of age (exercise for 19 weeks) showed significantly higher values during 10-min observational periods than Se-mice of the same age (Ex-mice vs. Se-mice; 361 ± 31 vs. 252 ± 30 counts, n = 8, p \ 0.05), suggesting that Ex-mice are relatively resistant to anxiety [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Habitual voluntary long-term exercise is believed to have a beneficial effect on human behavior and sleep [43,44]. Moreover, rodents using a running wheel voluntarily for a long period showed beneficial effects on behavior [45][46][47]. In a preliminary experiment on novelty-induced activity by means of an open-field test, Ex-mice at 25 weeks of age (exercise for 19 weeks) showed significantly higher values during 10-min observational periods than Se-mice of the same age (Ex-mice vs. Se-mice; 361 ± 31 vs. 252 ± 30 counts, n = 8, p \ 0.05), suggesting that Ex-mice are relatively resistant to anxiety [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, by comparing forced and voluntary wheel running, it was shown that both procedures increased behavioural and neurochemical indices of reward, which appeared elicited by distinct mechanisms possibly differentiating the motivation to exercise from its rewarding effects [9]. Furthermore, similar levels of forced and voluntary wheel running were found associated with an increase in hippocampal neurogenesis that was greater in the forced exercise group who also showed increased anxiogenic-like behaviour [10]. Thus, altogether these data suggest that the motivation to exercise can exert effects on brain and behaviour that are independent of exercise levels.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that intense physical activity subsequently alters behavior in the open-field, but the results are inconsistent, ranging from reduced (Duman et al 2008;Fuss et al 2010), unaffected (Leasure and Jones 2008), to increased locomotion (Burghardt et al 2004) in rodents after voluntary wheel running. Several environmental factors might have contributed to differences among those studies (e.g., the level of physical activity and housing conditions).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 99%